2005
DOI: 10.1021/bm050378v
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Mechanical Properties of Chitosan/Carbon Nanotubes Composites

Abstract: Biopolymer chitosan/multiwalled carbon nanotubes (MWNTs) nanocomposites have been successfully prepared by a simple solution-evaporation method. The morphology and mechanical properties of the chitosan/MWNTs nanocomposites have been characterized with field emission scanning electron microscopy (SEM), bright field transmission electron microscopy (TEM), optical microscopy (OM), wide-angle X-ray diffraction (XRD), and tensile as well as nanoindentation tests. The MWNTs were observed to be homogeneously disperse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
317
1
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 594 publications
(340 citation statements)
references
References 46 publications
20
317
1
2
Order By: Relevance
“…In addition, it has been demonstrated that hydrogen bonds can be formed among SWNTs and chitosan, thus allowing them to form a strong matrix with stronger mechanical properties for loadbearing applications. 9,38 Another advantage of B-SWCNT is their improved electrical conductivity. It is well known that electrical stimulation can promote osteogenesis at defective bone sites so B-SWCNT, with their improved electrical conductivity and excellent cytocompatibility properties, hold great potential for application in bone tissue engineering.…”
Section: A B C Dmentioning
confidence: 99%
“…In addition, it has been demonstrated that hydrogen bonds can be formed among SWNTs and chitosan, thus allowing them to form a strong matrix with stronger mechanical properties for loadbearing applications. 9,38 Another advantage of B-SWCNT is their improved electrical conductivity. It is well known that electrical stimulation can promote osteogenesis at defective bone sites so B-SWCNT, with their improved electrical conductivity and excellent cytocompatibility properties, hold great potential for application in bone tissue engineering.…”
Section: A B C Dmentioning
confidence: 99%
“…To date, cross-linking techniques have been used to increase mechanical strength of hydrogels, but these techniques result in only a moderate enhancement and sometimes even a lowered adsorption capacity 9 . Recently, carbon nanotubes (CNTs) have received special interest as one of the most promising nano-fi llers into polymer matrices for enhancement of its mechanical property [10][11][12] . In fact, as a result of the early report concerning the preparation of a CNTs/polymer composite by Ajayan et al 13 , many efforts have been made to combine CNTs and polymers to produce functional composite materials with superior properties 14, 15 .…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18] Poly(L-lactide) (PLLA) has attracted much attention because it is biodegradable, biocompatible, producible from renewable resources, and nontoxic to the human body and the environment. Recent innovation on the production process has lowered significantly the production cost, which further stimulates the studies on its property and potential applications.…”
Section: Introductionmentioning
confidence: 99%